Factors Influencing Transitions Between Frailty States in Elderly Adults: The Progetto Veneto Anziani Longitudinal Study. Issue 1 (14th November 2016) - Trevisan, Caterina; Veronese, Nicola; Maggi, Stefania; Baggio, Giovannella; Toffanello, Elena Debora; Zambon, Sabina; Sartori, Leonardo; Musacchio, Estella; Perissinotto, Egle; Crepaldi, Gaetano; Manzato, Enzo; Sergi, Giuseppe
Abstract : Objectives: To investigate frailty state transitions in a cohort of older Italian adults to identify factors exacerbating or improving frailty conditions. Design: Population‐based longitudinal study with mean follow‐up of 4.4 years. Setting: Community. Participants: Individuals enrolled in the Progetto Veneto Anziani (Pro.V.A.) (N = 2, 925; n = 1, 179 male, n = 1, 746 female; mean age 74.4 ± 7.3). Measurements: Frailty was identified at baseline and follow‐up based on the presence of at least three Fried criteria; prefrailty was defined as the presence of one or two Fried criteria. Anthropometric, socioeconomic, and clinical characteristics were assessed at baseline in a personal interview and clinical examination using validated scales and medical history. Results: During the study period, 1, 114 (38.1%) subjects retained their baseline frailty status, 1, 066 (36.4%) had a transition in frailty status, and the remainder of the sample died. Older age, female sex, obesity, cardiovascular disease, osteoarthritis, smoking, loss of vision, low levels of self‐sufficiency and physical performance, cognitive impairment, hypovitaminosis D, hyperuricemia, and polypharmacy were associated with increasing frailty and greater mortality. Conversely, overweight, low to moderate drinking, high educational level, and living alone were associated with decreasing frailty. Conclusions: Frailty was confirmed as a dynamic syndrome, with socioeconomic and clinical factors that could be targets of preventive actions influencing transitions to better or worse frailty status.